Research on Development Strategy of China’s Technology Transfer Based on SWOT-QSPM Model - Liu, Yu; Fang, Shu; Xu, Wenjuan; Lu, Ying; Yang, Zhiping; Hou, Huanhuan (Qualitative and Quantitative Methods in Libraries; Vol 8 No 3 (2019): September 2019 Issue, 2019)
[ Purpose/significance ] This paper used SWOT-QSPM model to explore the most suitable development strategy for China's technology transfer. Then, it studied the priorities of the various implementation options in this strategy, and proposed countermeasures. It provided theoretical models for the future research development of China’s technology transfer. [ Method/process ] This paper comprehensively investigated the four influencing factors of advantages, disadvantages, opportunities and threats of China's technology transfer development status. Furthermore, it used the SWOT model to deeply analyze the development environment, relationship and trend of China's technology transfer, and thus obtained the most suitable development strategy. Then QSPM matrix was used to determine the priority of the four alternative options for this strategy, and finally it formulated countermeasures for implementation. [ Result/conclusion ] The most suitable competitive strategy for China's technology transfer was in a good development situation in which advantages and opportunities occupied a dominant position. And the most suitable strategy for future development was the SO aggressive strategy. What’s more, the four options were in order of priority, followed by policy guidance, demand orientation, integrate development and service escort.